Orbital Infections and Infestations - A Narrative Review - Kaur, Apjit; Ankita (Nepalese Journal of Ophthalmology, 2023)
Introduction: Orbital infections and infestations present with varying clinical presentations and incidences ranging from benign ocular condition to disseminated systemic disease. The diagnosis is often difficult initially, due to similar ocular presentations. Materials and methods: This review was compiled using articles available on PubMed using key words like orbital infections, orbital cellulitis, orbital infestations, orbital tuberculosis, orbital fungal infections. Clinical experience in presentation and management at our centre was also included. Results: The varied presentations, management, complications and follow-ups have been summarised in this review. Conclusion: As the management is cause-specific, thus lies the importance of early accurate diagnosis, both clinical and radiological. This article aims to review existing literature on orbital infections and infestations for aiding in early accurate diagnosis and management.